2022
DOI: 10.1021/acsmeasuresciau.2c00042
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic and Microbial Electrochemistry: Approaches and Methods

Abstract: The coupling of enzymes and/or intact bacteria with electrodes has been vastly investigated due to the wide range of existing applications. These span from biomedical and biosensing to energy production purposes and bioelectrosynthesis, whether for theoretical research or pure applied industrial processes. Both enzymes and bacteria offer a potential biotechnological alternative to noble/rare metal-dependent catalytic processes. However, when developing these biohybrid electrochemical systems, it is of the utmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 251 publications
(432 reference statements)
0
22
0
Order By: Relevance
“…The quantitative evaluation of R. capsulatus cells viability in presence of 2,4‐DNP was then performed by spectrofluorimetry by utilizing fluorescein diacetate [38] . The fluorescence spectra and the histograms presented in Figure 4 demonstrated that the long exposure to 2,4‐DNP (trace 2, R.caps ‐PDA+300.0 μM 2,4‐DNP) did not result in a complete inhibition of bacteria viability, since a clear fluorescence emission signal was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative evaluation of R. capsulatus cells viability in presence of 2,4‐DNP was then performed by spectrofluorimetry by utilizing fluorescein diacetate [38] . The fluorescence spectra and the histograms presented in Figure 4 demonstrated that the long exposure to 2,4‐DNP (trace 2, R.caps ‐PDA+300.0 μM 2,4‐DNP) did not result in a complete inhibition of bacteria viability, since a clear fluorescence emission signal was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The quantitative evaluation of R. capsulatus cells viability in presence of 2,4-DNP was then performed by spectrofluorimetry by utilizing fluorescein diacetate. [38] The fluorescence spectra and the histograms presented in Figure 4…”
Section: Effect Of 24-dnp On Photobioelectrocatalysismentioning
confidence: 99%
“…The current generated upon application of a potential provides kinetic and mechanistic information about the enzyme object of study. CV can offer insights on the type of electron transfer (ET) mechanism, direct or mediated, of both enzymes and electrogenic microbes . CV can be used to detect the presence of membrane bound redox proteins responsible for ET in electroactive bacteria and their redox potential .…”
Section: Recent Examples About the Application Of Electroanalytical T...mentioning
confidence: 99%
“…The adsorption of electrochemically active molecules and the capacitive charge that is created when microbial systems are used, can indeed also contribute to the total charge consumed at the electrode . SWV, by reducing nonfaradaic contributions, allows a more accurate calculation of k ET and electroactive surface coverage …”
Section: Recent Examples About the Application Of Electroanalytical T...mentioning
confidence: 99%
“…The combination of electrochemical and microbial as well as enzymatic reactions is well-established in the field of biosensors (Bedendi et al, 2022). In bioeconomy in general, this combination is believed to be highly effective to optimize established processes or to setup new production routes (Harnisch & Urban, 2018).…”
Section: Introductionmentioning
confidence: 99%